The development potential and impacts of commercial Eucalyptus woodlots in selected areas of Kwazulu, South Africa - Cellier, Guy Anthony (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.) -- University of Stellenbosch, 1994.